KEMANUSIAAN-SUBSTITUSIONAL KRISTUS DALAM PEMIKIRAN THOMAS F. TORRANCE - Yeremia Yordani Putra (Jurnal Amanat Agung, 2020)
Abstract: This paper focuses on Thomas F. Torrance's thought on the Vicarious Humanity of Christ. Torrance understands that the redemptive work of Christ is not restricted to the moment of His death on the cross, but is in all moments of His human life. Torrance places great emphasis on the understanding that Christ in His humanity stands in our place and represents us before God the Father. Through His obedience, Christ restored the humanity of sinful believers as a perfect response to God. This truth stresses that Christ's redemption is not just a matter of the forgiveness of sins, but also is the bestowing of a restorative impact on the whole being of the believers. Therefore, the Vicarious Humanity of Christ becomes the ontological basis for the life of the believers. This thought gives great significance to the lives of believers, including the aspects of faith, repentance, and worship. Keywords: The Vicarious Humanity of Christ, Fallen Humanity, Perfect Response, Thomas F. Torrance. Abstrak: Tulisan ini menyoroti pemikiran Thomas F. Torrance mengenai Kemanusiaan-Substitusional Kristus. Torrance memahami karya penebusan Kristus bukan hanya dibatasi pada momen kematian-Nya di atas kayu salib, melainkan dalam seluruh momen kehidupan-Nya sebagai manusia. Torrance sangat menekankan pemahaman bahwa Kristus dalam kemanusiaan-Nya berdiri di tempat kita dan mewakili kita di hadapan Allah Bapa. Melalui ketaatan-Nya, Kristus memulihkan kemanusiaan orang percaya yang telah berdosa sebagai respons sempurna kepada Allah. Kebenaran ini menegaskan bahwa penebusan Kristus bukan hanya soal pengampunan dosa, tetapi juga penganugerahan dampak restoratif pada seluruh keberadaan diri orang percaya. Oleh karena itu, Kemanusiaan-Substitusional Kristus menjadi dasar ontologis bagi kehidupan orang percaya. Pemikiran ini memberikan signifikansi yang besar bagi kehidupan orang percaya, di antaranya dalam aspek iman, pertobatan, dan ibadah. Kata-kata kunci: Kemanusiaan-Substitusional Kristus, Kemanusiaan Berdosa, Respons Sempurna, Thomas F. Torrance